Effect of external magnetic field on tribological properties of goethite (a-FeOOH) based nanofluids. (November 2018) - Zin, V.; Agresti, F.; Barison, S.; Litti, L.; Fedele, L.; Meneghetti, M.; Fabrizio, M.
Abstract: Additives responsive to magnetic fields can be easily manipulated under the action of external stimuli and employed in various sectors, with great feasibility. In this work, suspensions of goethite nanorods were developed for anti-friction and anti-wear purposes. Goethite represents a promising additive in lubricants promoting the formation of a protective tribofilm during rubbing processes, especially under severe lubrication regime. Nanofluids were characterized regarding both viscosity and stability. Tribological ball-on-flat tests were executed in presence of variably oriented magnetic field. The resulting orientation of nanorods within the contact zone influenced the friction coefficient with a maximum decrease of 22% with magnetic field oriented parallel to the sliding direction. The wear mechanism was investigated by means of SEM, X-EDS and Raman spectroscopy. Highlights: Goethite-based nanofluids were studied for anti-friction and anti-wear purposes. Goethite nanorods were used as magnetic responsive additives for nanolubricants. Variably oriented magnetic field affects nanofluids tribological behaviour. Free nanorods having high motion freedom were more effective in reducing wear. Tribochemical evolution of nanorods results in protective oxidized tribofilm.